Contribution of Bistability and Noise to Cell Fate Transitions Determined by Feedback Opening. Issue 20 (9th October 2016) - Hsu, Chieh; Jaquet, Vincent; Maleki, Farzaneh; Becskei, Attila
Abstract: Alternative cell fates represent a form of non-genetic diversity, which can promote adaptation and functional specialization. It is difficult to predict the rate of the transition between two cell fates due to the strong effect of noise on feedback loops and missing parameters. We opened synthetic positive feedback loops experimentally to obtain open-loop functions. These functions allowed us to identify a deterministic model of bistability by bypassing noise and the requirement to resolve individual processes in the loop. Combining the open-loop function with kinetic measurements and reintroducing the measured noise, we were able to predict the transition rates for the feedback systems without parameter tuning. Noise in gene expression was the key determinant of the transition rates inside the bistable range. Transitions between two cell fates were also observed outside of the bistable range, evidenced by bimodality and hysteresis. In this case, a slow transient process was the rate-limiting step in the transitions. Thus, feedback opening is an effective approach to identify the determinants of cell fate transitions and to predict their rates. Graphical Abstract: Highlights: The rates of transition between two cell fates or states are difficult to predict because of missing parameters and the strong effect of noise. We predict the rates with a method termed feedback opening; the predictions are in good agreement with the observed rates. When feedback loops are opened experimentally, the resulting open-loop function determines whether the parent feedback loop has one or two stable states. Hysteresis may be absent in bistable feedback loops.